Fundamental assumptions as predictors of psychological hardiness of students with disabilities - Kuprieieva, Olga; Traverse, Tetiana; Serdiuk, Liudmyla; Chykhantsova, Olena; Shamych, Oleksandr (Social Welfare: Interdisciplinary Approach, 2020)
The article describes the psychological study determining the factors that support fundamental assumptions of students with disabilities. We have determined correlations between psychological hardiness of students with disabilities and their system of fundamental assumptions; beliefs in the benevolence of the surrounding world and people, in the meaningfulness of some events, in a chance to build successfully one’s own life and in one’s own luck have a significant influence on psychological hardiness. The predictors of psychological hardiness of students with disabilities are: positive interactions with the outside world; self-acceptance as a conscious acceptance of various aspects of one’s own personality; personal autonomy, which allows an individual to independently determine their own behaviour, assess adequately their capabilities and resist external influences.
Keywords: fundamental assumptions; psychological hardiness; self-acceptance; positive self-attitude; self-efficacy; personal autonomy; disabled students